Kaum Kedar: Tanggung Jawab Orang Percaya - Yeheskiel Obehetan (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2023)
This study aimed to explore the mission of believers in sharing the gospel to the Kedar communities. Using library research method, the analysis find out: 1) The responsibilities of believers (loving and praying); 2) Reaching Kedar as the proof of the responsibility (mobilization, regeneration, and facilitate; and 3) Responsible parties (Theological seminary, church, missionary organization, communities, and all believers) A comprehensive understanding and responsibilities as believers could enable the disciples to have a new perspective about Kedar, also taking part in contextual evangelism, so Kedar communities could accept the Good News.